JOURNAL OF GOVERNMENT & POLITICS : Patronage Politics and Clientelism in Housing Welfare: The Case of Gawad Kalinga (GK) Villages in Paranaque City, The Philippines - Prince Aian G. Villanueva, Jessa Nicole P. Salazar (FISIPOL UMY, 2015)
Patronage politics has become a defining characteristic of the Philippine political landscape.